Preventive Measures of Ventilator-Associated Pneumonia among Intensive Care Unit Nurses: Tindakan Pencegahan Pneumonia Terkait Ventilator di antara Perawat Unit Perawatan Intensif - Saja Kareem Jassim (Academia Open, 2024)
General Background: Ventilator-associated pneumonia (VAP) significantly prolongs intensive care unit (ICU) hospitalizations, elevating healthcare costs and increasing mortality risk. Specific Background: Despite existing knowledge of VAP's impact, there is limited research on the preventative practices of ICU nurses, a critical factor in mitigating this condition. Knowledge Gap: This study explores ICU nurses' preventive measures for VAP and their correlation with demographic characteristics, highlighting a gap in literature. Results: Conducted from November 1, 2023, to April 10, 2024, at Basrah hospitals, the study involved 93 purposively sampled ICU nurses. The findings revealed that 48.4% of participants exhibited moderate preventive behavior, while 39.8% displayed poor preventive behavior. Notably, a significant relationship was found between the preventative behavior scores and the education level, as well as years of service in the ICU. Novelty: The study provides valuable insights into the current VAP prevention practices among ICU nurses, highlighting demographic factors that influence these behaviors. Implications: The study highlights the need for educational interventions to improve ICU nurses' preventative practices, potentially reducing VAP incidence and improving patient outcomes in intensive care settings. Higlights: Moderate Preventive Behavior: 48.4% of ICU nurses showed moderate VAP prevention practices. Demographic Relationships: Education level and service years influence preventive behavior scores. Training Necessity: Targeted education needed to improve VAP prevention among ICU nurses. Keywords: Ventilator-associated pneumonia, ICU nurses, preventive practices, demographic characteristics, patient outcomes.